2022
DOI: 10.48550/arxiv.2205.07641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust structured light in atmospheric turbulence

Abstract: Structured light is routinely used in free space optical communication channels, both classical and quantum, where information is encoded in the spatial structure of the mode for increased bandwidth. Unlike polarisation, the spatial structure of light is perturbed through such channels by atmospheric turbulence, and consequently, much attention has focused on whether one mode type is more robust than another, but with seemingly inconclusive and contradictory results. Both real-world and experimentally simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Structured light is a very general term but will be restricted in this context to referring to any light fields with strong spatial inhomogeneity of amplitude, phase, polarization, and other parameters [10]. Following this definition, it has been shown that structured light provides unique capabilities with regards to probing through turbulent media [11]. Another study shows that other forms of structured light with polarization invariant properties are more resilient in non-ideal propagation conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Structured light is a very general term but will be restricted in this context to referring to any light fields with strong spatial inhomogeneity of amplitude, phase, polarization, and other parameters [10]. Following this definition, it has been shown that structured light provides unique capabilities with regards to probing through turbulent media [11]. Another study shows that other forms of structured light with polarization invariant properties are more resilient in non-ideal propagation conditions [12].…”
Section: Introductionmentioning
confidence: 99%